Honoring primary education for stateless children: analysis of Malaysian legal perspective and current practice - Md Saman, Mazura; Mohd Badrol Afandi, Nor Hafizah (Zes Rokman Resources, 2018)
Article 28 of the United Nation Convention on the Rights of the Child (CRC) 1989 recognise the right of a child to education. It urges nations to imperatively making primary education obligatory and freely accessible for all. This paper, which employ content analysis and library research, seeks to analyse the statutory provisions with regards to primary education, the implementation and limitation of free education for stateless children in Malaysia. The research is driven by the increased numbers of stateless children in Malaysia. However, they are denied entry into public school. The significant of the research is to look into the prevailing Malaysian law regarding access to education which provide answer to the hindrance for the stateless children to be admitted into public school. The key finding of the research indicates that while children are guaranteed of free primary education, it is meant only for Malaysian citizenship holder. Constitutional safeguard with regard to education was not extended to the stateless children. Currently, the primary education for the children of stateless refugees and stateless children of irregular migrants, are being cared by the Non-Governmental Organisation (NGOs). However only a few lucky groups of these children are able to receive primary education provided by the NGO’s. Many other groups of stateless children were left unattended. Since Malaysia has ratified the CRC in 1995, it is commendable for the policy maker to ensure moves being taken to honour the ratification, thus granting the most important basic rights for children, that is, primary education legally accessible for all.